2014
DOI: 10.1073/pnas.1402584111
|View full text |Cite
|
Sign up to set email alerts
|

Endemism and functional convergence across the North American soil mycobiome

Abstract: Identifying the ecological processes that structure communities and the consequences for ecosystem function is a central goal of ecology. The recognition that fungi, bacteria, and viruses control key ecosystem functions has made microbial communities a major focus of this field. Because many ecological processes are apparent only at particular spatial or temporal scales, a complete understanding of the linkages between microbial community, environment, and function requires analysis across a wide range of scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
437
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 462 publications
(482 citation statements)
references
References 68 publications
(68 reference statements)
36
437
2
1
Order By: Relevance
“…These results support our initial hypothesis and provide direct evidence for the microbial regulation of soil processes linked to C degradation in terrestrial ecosystems. Our results suggest environmental filters are primary responsible for the assembly of soil microbial community and determine the strong differences in the community composition between different geographic regions (Fierer et al, 2013;Talbot et al, 2014). However, the functional potential of the microbial community will be driven by the selection of active taxa within different lineages.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…These results support our initial hypothesis and provide direct evidence for the microbial regulation of soil processes linked to C degradation in terrestrial ecosystems. Our results suggest environmental filters are primary responsible for the assembly of soil microbial community and determine the strong differences in the community composition between different geographic regions (Fierer et al, 2013;Talbot et al, 2014). However, the functional potential of the microbial community will be driven by the selection of active taxa within different lineages.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, this strong correlation also indicates that functional genes can be used to develop a gene-centric approach to integrate environmental genomics into simulation models in order to improve their predictive power and accuracy of ESMs (Reed et al, 2014). Regulatory pathways of the activity of enzymes involved in C degradation Identifying the structural-functional relationships for microbial organisms is particularly critical to determine the importance of the soil microbial community in regulating ecosystem processes, and thus there is keen interest in developing theoretical and experimental approaches to disentangle the microbial regulation of soil functions from other biotic and abiotic drivers (for example, Strickland et al, 2009;Wallenstein and Hall, 2012;Talbot et al, 2014;You et al, 2014;Wood et al, 2015). Albeit we found that functional genes were strongly related to enzyme activities, these results are correlative in nature and hence potentially non-causative.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations